(untitled) (Journal of EAHIL, 2015)
Greetings. I thought it would be appropriate to begin this inaugural News Update with a brief overview ofÂ the US National Library of Medicine (NLM). With this piece, I’m giving you a “big picture” view of theÂ Library, but you are welcome and encouraged to delve deeper into the history and...